A novel TLR4 binding protein, 40S ribosomal protein S3, has potential utility as an adjuvant in a dendritic cell-based vaccine. Issue 1 (28th February 2019) - Park, Hyun Jin; Jang, Gun-Young; Kim, Young Seob; Park, Jung Hwa; Lee, Sung Eun; Vo, Manh-Cuong; Lee, Je-Jung; Han, Hee Dong; Jung, In Duk; Kang, Tae Heung; Park, Yeong-Min
Abstract : Background: Dendritic cells (DCs) are professional antigen presenting cells (APCs), which can activate antigen-specific CD8+ T cell immunity, resulting in tumor clearance. Immature DCs are usually stimulated by various adjuvants through their immune receptors. Among them, Toll-like receptor 4 (TLR4) has an important role in activating DCs to cause their maturation. In fact, TLR4 is well-known to induce innate and adaptive immune responses against various external microbial or internal damage associated molecular patterns (DAMP). LPS is widely regarded as a strong stimulator of TLR4 signaling. However, LPS is inappropriate for use in humans since it is an endotoxin. Unfortunately, other TLR4 ligands such as HMGB1 or heat shock proteins have weak adjuvant effects. Therefore, there is a need to identify novel, biocompatible, strong, TLR4 ligands. Methods: 40S ribosomal protein S3 (RPS3) was screened through pull-down assay using TLR4. BMDCs from wild type (WT) and TLR4 knock-out mice were treated by RPS3 to identify the activation and maturation of DCs. T cell generation including memory T cells, tumor prevention, and treatment experiments were performed with BMDCs based vaccination. Also, human DCs originated from patients were treated by RPS3 to confirm the activation and maturation of DCs. Results: In this study, we identified 40S ribosomal protein S3 (RPS3) through a pull-down assay using a variety of human cancer cell-derived proteins that could bind to TLR4. RPS3 was released from tumor cells following treatment with an anticancer drug, and it was shown that the released RPS3 binds to TLR4. Recombinant RPS3 induced maturation and activation of DCs, and following pulsing with tumor specific antigens, these DCs could be used as a vaccine to significantly increase tumor specific CD8 + IFN-γ + T cells, and provide both tumor prevention and tumor treatment effects. The effect of RPS3 on DC maturation and its utility as a vaccine were shown to be dependent on TLR4 using TLR4 knockout mice. Conclusions: This study therefore proved that human cancer cell-derived RPS3, a novel TLR4 ligand, has great potential as an adjuvant in tumor-specific antigen DC-based vaccines.